Study Of Music Performance The Orches Group Pancaran Senja Melayu Village Batu Besar Nongsa Batam - Rivaldi Ihsan (Universitas Negeri Medan, 2022)
The study of musical performances in this study focuses on the musical performance itself. Where music performance events are present through two important roles, namely musicians and audiences who are the center when the music performance takes place. The success of a musical performance is through a procession of intense rehearsals, ongoing performances, and evaluations after musical performances. This study is a qualitative analytic description of the Pancaran Senja Malay Orchestra music group at Kampung Melayu Batu Besar Nongsa Batam. The research methods are field observations, interviews, literature studies, and participant observers. The results of the research are; that the success of the Pancaran Senja Malay Orchestra music performance until now has gone through the stages of the rehearsal process, show flight hours, and performance evaluation for the progress of the Pancaran Senja Malay Orchestra. This procession was born through discussion and agreement among fellow musicians, so that the continuity and survival of the Pancaran Senja Malay Orchestra music group was established.